Mindsight : the new science of personal transformation - Siegel, Daniel J., 1957- (New York : Bantam Books, 2010)
Inspiring and informative,'Mindsight' offers exciting new proof that people aren't hardwired to behave in certain ways, but instead have the ability to harness the power of their minds to resculpt the neural pathways of their brains.
Includes bibliographical references (p. [271]-300) and index.
Keywords: Mind and body therapies; Mind and body; Mindfulness-based cognitive therapy